Leveraging health information exchange for clinical research: Extreme underreporting of hospital service utilization among patients with substance use disorders. (1st July 2020) - Gryczynski, Jan; Nordeck, Courtney D.; Martin, Ross D.; Welsh, Christopher; Schwartz, Robert P.; Mitchell, Shannon Gwin; Jaffe, Jerome H.
Highlights: Health information exchange (HIE) can yield high-quality data on health services. HIE identified inpatient, ED visits in a sample with high-volume, fragmented care. Utilization review via HIE was far superior to self-report and single-system HER. HIE has considerable utility for clinical and services research. Abstract: Background: Substance use disorders are associated with inefficient and fragmented use of healthcare services. The Chesapeake Regional Information System for Our Patients, Inc. (CRISP) is a Health Information Exchange (HIE) linking disparate systems of care in the mid-Atlantic region. Methods: This article describes applications of HIE for tracking hospital service utilization in substance use disorder clinical and services research, drawing upon data from one of the first studies approved to access the CRISP HIE. Participants were 200 medical/surgical inpatients with comorbid opioid, cocaine, and/or alcohol use disorder (45.5 % female; 56.5 % black; 77.5 % opioid use disorder; 42.0 % homeless). This study compared HIE-identified hospital service utilization with conventional methods of participant self-report during in-person research follow-ups (3-, 6-, and 12-months post-discharge) and electronic health record (EHR) review from the hospital system of the index admission. Results: This sample exhibited high levels of hospital utilization, which would have been underestimated using conventional methods. Relying exclusively on self-report in the 12-month observation period would have identified only 33.8 % of 429 inpatient hospitalizations and 9.0 % of 1, 287 ED visits, due to both loss-to-follow-up and failure to report events. Even combining self-report with single-system EHR review identified only 66.2 % of inpatient hospitalizations and 59.8 % of ED visits. Conclusions: CRISP HIE data were superior to conventional methods for ascertaining hospital service utilization in this sample of patients exhibiting high-volume and fragmented care. The use of HIE holds implications for improving rigor, safety, and efficiency in research studies.